Pharmaceutical manufacturing encyclopedia - Sittig, Marshall (Noyes Publications, 1988)
Descriptions of 1295 pharmaceuticals now being marketed under trade names somewhere throughout the world. Information was obtained from the patent literature. Alphabetical arrangement by generic names. Each entry gives therapeutic function; chemical, common, and trade names; structural formula; country; year of introduction; manufacture; raw materials; manufacturing process; and references. Trade name, raw materials indexes. 1st ed., 1979.
Keywords: Drugs -- Synthesis -- Dictionaries.; Pharmaceutical chemistry -- Dictionaries.; Drugs -- Dictionaries.; Drugs.; elektronické knihy; electronic books